Electrically and Optically Controllable p–n Junction Memtransistor Based on an Al2O3 Encapsulated 2D Te/ReS2 van der Waals Heterostructure. Issue 12 (5th November 2021) - Nguyen, Duc Anh; Jo, Yongcheol; Tran, Thi Uyen; Jeong, Mun Seok; Kim, Hyungsang; Im, Hyunsik
Abstract: The exploration of memtransistors as a combination of a memristor and a transistor has recently attracted intensive attention because it offers a promising candidate for next‐generation multilevel nonvolatile memories and synaptic devices. However, the present state‐of‐the‐art memtransistors, which are based on a single material, such as MoS2 or perovskite, exhibit a relatively low switching ratio, require extremely high electric fields to modulate bistable resistance states and do not perform multifunctional operations. Here, the realization of an electrically and optically controllable p–n junction memtransistor using an Al2 O3 encapsulated 2D Te/ReS2 van der Waals heterostructure is reported. The hybrid memtransistor shows a reversible bipolar resistance switching behavior between a low resistance state and a high resistance state with a high switching ratio up to 10 6 at a low operating voltage (<10 V), high cycling endurance, and long retention time. Moreover, multiple resistance states are achieved by applying different bias voltages, gate voltages, or light powers. In addition, logical operations, including the inverter and AND/OR gates, and synaptic activities are performed by controlling the optical and electrical inputs. The work offers a novel strategy for the reliable fabrication of p–n junction memtransistors for multifunctional devices and neuromorphic applications. Abstract : An electrically and optically tunable p–n junction memtransistor is fabricated using an Al2 O3 encapsulated 2D Te/ReS2 van der Waals heterostructure. The hybrid memtransistor exhibits a low‐voltage operation, being electrically and optically controllable, and having highly rectifying characteristics, and successfully functions as both multi‐terminal nonvolatile memory and multivalued logic gates.